Spray‐Dried Photonic Balls with a Disordered/Ordered Hybrid Structure for Shear‐Stress Indication. Issue 48 (17th October 2022) - Wenderoth, Sarah; Bleyer, Gudrun; Endres, Jakob; Prieschl, Johannes; Vogel, Nicolas; Wintzheimer, Susanne; Mandel, Karl
Abstract: Optical microscale shear‐stress indicator particles are of interest for the in situ recording of localized forces, e.g., during 3D printing or smart skins in robotic applications. Recently developed particle systems are based on optical responses enabled by integrated organic dyes. They thus suffer from potential chemical instability and cross‐sensitivities toward humidity or temperature. These drawbacks can be circumvented using photonic balls as shear‐stress indicator particles, which employ structural color as the element to record forces. Here, such photonic balls are prepared from silica and iron oxide nanoparticles via the scalable and fast spray‐drying technique. Process parameters to create photonic balls with a disordered core and an ordered particle structure toward the exterior of the supraparticles are reported. This hybrid disordered–ordered structure is responsible for a color loss of the indicator particles during shear‐stress application because of irreversible structural destruction. By adjusting the primary silica particle sizes, nearly all colors of the visible spectrum can be achieved and the sensitivity of the response to shear stress can be adjusted. Abstract : Shear‐stress indicators in the micrometer range, where stress can be detected with the bare eye, are suitable for various applications. For this purpose, supraparticles in form of photonic balls with a disordered–ordered core–shell hybrid structure are investigated. With increasing shear stress, the ordered shell is gradually destroyed and the intense color disappears stepwise.